The CONCURRENT DESCENDING MESOCOLON, OVARY AND ANTERIOR ABDOMINAL WALL; A RARE PRESENTATION OF EXTRAUTERINE ADENOMYOMA - mohd shamsudin bin zainol abidin (British Journal Of Surgical Science, 2022)
Extrauterine adenomyoma is an extremely rare condition with no known incidence rate. It is a noncancerous tumour that develops from smooth muscle and endometriotic tissue. We present a case of a 42-year-old woman who had a past history of myomectomy for uterine fibroid and presented with a growing left sided abdominal tumour for 3 years. A CT scan of the abdomen revealed several heterogeneous masses affecting the descending mesocolon, ovary, and anterior abdominal wall. An ultrasound-guided tru-cut biopsy of a left iliac fossa intraperitoneal tumour confirmed the diagnosis of extrauterine adenomyoma. She had a segmental descending colon resection with side-to-side anastomosis, as well as additional lesions removed. Despite the rarity of the occurrence, clinical, imaging, and histological examinations remain the primary diagnostic modalities.